The utilization of oil palm empty fruit bunch (Opefb) fibre in home compost making - Vanessa Carmel Lopez (2022)
Malaysia is known to be the second largest global producer of palm oil after Indonesia. Every year, millions of tons of oil palm waste are produced where OPEFB which is produced at the palm oil mills covers the largest portion of waste. Improper management of OPEFB can lead to many environmental problems. Therefore, composting is considered as an effective method for waste management. However, composting of OPEFB takes a long time due to its high lignin and cellulose content. Therefore, in this research, home-based composting of OPEFB fibres was carried out with the incorporation of home-made EM solution. There were three objectives of this research. The first objective was to prepare home-made compost by using OPEFB fibre. Composting of OPEFB fibre was carried out by using aerobic composting method together with garden waste which is dried leaves and kitchen waste which is vegetable scraps. The second objective was to determine the effects of different amounts of OPEFB fibre on the duration of composting. A total of nine compost samples with different amounts of OPEFB fibre was made which had different duration of composting of 4 to 8 weeks. EM solution was added to the replicated compost samples to aid in the decomposition of OPEFB fibre and to provide nutrients to the compost mixture. Based on the results obtained, it was proven that compost containing higher amounts of OPEFB fibre took a longer time to mature. Compost sample made from 100 % OPEFB fibre took 8 weeks of composting period while its replicate sample which was treated with EM took 7 weeks for composting. Finally, the objective was to investigate the effectiveness of home-made compost to support plant growth of bird's-eye chili. The planting medium was prepared with a ratio of 3: 1: I of soil, compost and cocopeat. Cocopeat was added to the top layer to regulate moisture of the soil. Based on the results, soil treated with compost containing OPEFB fibres showed better results for plant growth compared to soil that was treated without compost and with controlled sample of compost (0 % OPEFB fibre). It was also proven that compost treated with EM containing 14 % OPEFB fibre and 86 % vegetable scraps with an initial C: N ratio of 29.9: 1 showed the best result on plant growth. Therefore, based on this research, compost made from OPEFB fibre can be utilized as a growing medium to support plant growth. Finally, home-based composting is a practice which can be carried out to create awareness among Malaysians that waste management can actually begin from home before this effort can be developed at a higher scale. Keywords: OPEFB fibre, home-based composting, aerobic composting. EM solution, bird's-eye chilies.